PENINGKATAN HASIL BELAJAR MEMBACA PEMAHAMAN DENGAN STRATEGI PEMBELAJARAN INSTAN ASSESSMENT PADA PELAJARAN BAHASA INDONESIA SISWA KELAS VI SDN 028 ROKAN IV KOTO - nurwati nurwati (STKIP ROKANIA, 2018)
This study aims to improve the learning ourtcomes of reading comprehension on the Indonesian language subjects students of class VI SDN 028 Rokan IV Koto Rokan Hulu. Result of research, that is the improvement of learning result read student comprehension from before action to cycle I and cycle II. At the before the result of learning result of reading comprehension of student only reach 67.05% with medium category. In the first cycle the learning achievement of reading comprehension of students has reached 70.23%, although not yet reached the completeness of individual or group, but the result of learning to read student understanding on cycle I increased from 67.05% to 70,23%. After the improvement of teacher and student activity in cycle II, the result of learning to read the students' comprehension is quite satisfactory by reaching an average of 77.50%.